2007
DOI: 10.1115/1.2786489
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies in the Vibration Induced by the Rotor Stator Interaction in a Centrifugal Pump Turbine

Abstract: The highest vibration levels in large pump turbines are, in general, originated in the rotor stator interaction (RSI). This vibration has specific characteristics that can be clearly observed in the frequency domain: harmonics of the moving blade passing frequency and a particular relationship among their amplitudes. It is valuable for the design and condition monitoring to count on these characteristics. A CFD model is an appropriate tool to determine the force and its characteristics. However, it is time con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 11 publications
1
85
0
Order By: Relevance
“…The main excitation force for this type of machine comes from the pressure fluctuation induced by the rotor-stator interaction (RSI) [3][4][5]. The RSI arises from the interference between the rotating blades of the runner and the stationary vanes.…”
Section: Origin Of Vibrationmentioning
confidence: 99%
“…The main excitation force for this type of machine comes from the pressure fluctuation induced by the rotor-stator interaction (RSI) [3][4][5]. The RSI arises from the interference between the rotating blades of the runner and the stationary vanes.…”
Section: Origin Of Vibrationmentioning
confidence: 99%
“…At low flow rates, especially, the separate flow structure may transfer from one blade channel to the adjacent channel forming rotating stall phenomenon [10]. In centrifugal pump, flow out of impeller interacts with volute tongue periodically due to the limited blade number [11]. Rotor-stator interaction between impeller and volute tongue would cause pressure pulsating and nonuniform flow field distribution on periphery of impeller.…”
Section: Introductionmentioning
confidence: 99%
“…The phase-averaged velocity field, turbulence field and the blade orientation effects were quantitatively examined in detail. Some other research works [10][11][12][13][14][15][16][17][18][19][20] can be also found for the study of pressure fluctuation caused by periodical unsteady flow in centrifugal pumps. In reality, especially in some high risk applications in which the stability of centrifugal pump is the most important, the circular casing structure has been adopted to increase the reliability of overall structure of the high power pump.…”
Section: Introductionmentioning
confidence: 99%